Molecular biology of rotaviruses. VIII. Quantitative analysis of regulation of gene expression during virus replication. - Johnson, M A (1989)
A sensitive and quantitative solution hybridization assay recently developed in this laboratory has been applied to the study of the regulation of viral gene expression in rotavirus-infected cells. Measurement of the cumulative level of viral plus-strand (mRNA) synthesis at hourly intervals throughout the growth cycle has provided evidence for both quantitative and qualitative regulation of transcription. Qualitative control was found only when cycloheximide was used to block protein synthesis in infected cells, when transcription of four of the viral genes (genes 5, 6, 7, and 9) was independent of protein synthesis. Quantitative regulation was demonstrated by the accumulation of mRNA to much higher levels for some of the viral genes (e.g., genes 2 and 7) relative to others (e.g., genes 4 and 6). In addition to quantitative control at the level of transcription, measurement of the relative molar amounts of the various viral proteins at 6.5 h postinfection showed that their levels did not directly reflect those of their encoding RNAs, indicating the existence of translational control of gene expression in the rotavirus system. Analysis of the levels of minus strand synthesized for each viral gene showed that they were not all accumulated to the same level. The significance of this result in the light of the presumed similarities in replication strategy to that of the mammalian reoviruses is discussed.